Synergism of d-limonene and temozolomide on migratory and apoptotic behaviors of human glioblastoma cell lines - Megha Gautam; Reema Gabrani (BioImpacts)
Introduction: Glioblastoma (GBM), which is a heterogeneous and aggressive type of brain tumor, is known for its poor survival outcomes. The treatment of GBM remains challenging primarily due to the drug resistance to the current standard therapeutic option, temozolomide (TMZ). Researchers are currently focusing on developing an appropriate alternative combinatorial therapeutic to enhance treatment outcomes. D-limonene (DL) is a monoterpene derived from citrus fruit. This study aims to assess the impact of combining DL with TMZ and explore its potential mechanism of action in U87MG and LN229 GBM cells. Methods: The effects of the combined treatment of DL and TMZ were assessed on various cellular aspects, including cell viability, anchorage-independent cell growth, and DNA damage. Furthermore, the influence of this combination on cell cycle progression, cell migration, and cell death was also investigated. Results: The combination of DL+TMZ demonstrated a synergistic effect, resulting in reduced cell proliferation and suppressing the colony formation ability of a single cell. Treatment with DL and TMZ arrested the cells in G0/G1 phase. Furthermore, the DL+TMZ combination induced apoptosis by upregulating the expression of Bax, and Caspase (CASP)-3, while reducing the expression of the Bcl-2 gene in GBM cells. In addition, the combined treatment of DL+TMZ significantly decreased the expression of matrix metalloproteinase (MMP)-2 and MMP-9, expression, indicating inhibition of cell migration in GBM cells. Conclusion: In conclusion, the combination of DL and TMZ demonstrated a synergistic effect in reducing cell proliferation, suppressing colony formation, inducing apoptosis, and inhibiting cell migration in GBM cells. These findings suggest the potential of DL+TMZ combination therapy as an effective treatment for GBM.